Financing the lifecycle or mitigating poverty: Redistribution in the Hungarian welfare system by age and income - Rob́ert Ivań Gaĺ; Maŕton Medgyesi (Hungarian Demographic Research Institute, 2017)
There seems to be a general consent in the expert community that Hungarian social policy provides poorly targeted benefits and services that are prone to Mattheweffects. Our results confirm this observation but we also find that the data offer an alternative interpretation of what the Hungarian welfare state is actually doing. Instead of supporting the poor it reallocates resources from the working age population to children and elderly people. It functions as an intermediary between overlapping generations that seek to finance their lifecycle by exploiting the opportunity offered by the very overlap, the fact that contemporaries are of different age. In a cross-sectional framework we analyse reallocations by age and income simultaneously and assess the relative importance of these two variables in explaining the access and contribution to public benefits. Our data from 2010 (based on EU-SILC and the Household Budget Survey) covers public transfers (cash and in-kind) and both direct and indirect taxes. We compare the importance of age and income in explaining transfers and taxes in a regression-analysis framework by studying causal importance (comparing coefficients) and dispersion importance of the variables (using Shapley-value decomposition). We find that income is irrelevant in explaining access to benefits and services but age is important. On the contribution side, income proves as important as age. This qualifies our description of the Hungarian welfare system: it serves as a channel through which affluent people in their working age support people in inactive age of all income groups.
Keywords: I38; H29; 300; welfare state; decomposition of income inequalities; National Transfer Accounts; provision and effects of welfare programs; income redistribution; taxation and government expenditures; Sozialstaat; Öffentliche Sozialleistungen; Einkommensverteilung; Umverteilung; Shapley-Wert; Dekompositionsverfahren; Ungarn